The Implementation of GBA in Teaching Writing Recount Text - Ramadhani, Angelita; Nugraha, Sidik Indra; Pujiawati, Nia (PROJECT (Professional Journal of English Education), 2026)
For students in Indonesia, writing in English is often a big challenge, especially in organizing ideas, mastering text structure, and using appropriate vocabulary. This study aims to explore how students are facilitated in learning to write recount texts through the Genre-Based Approach (GBA) as well as to identify the challenges they face. The research used a qualitative method with a case study approach involving an English teacher and six ninth-grade students at a junior high school in Tangerang. The data were obtained through classroom observation, semi-structured interviews, and documentation, and were then analyzed using thematic analysis techniques. The results showed that students are facilitated through the GBA stages (BKOF, MOT, JCOT, ICOT), scaffolding, peers and teacher feedback, critical thinking and collaborative learning activities. It was also revealed that the students still face difficulties in understanding the structure of recount texts, choosing the right vocabulary, translating ideas from Indonesian to English, and writing the text independently. It was concluded that GBA was effective in supporting recount text writing skills, although additional intervention related to vocabulary mastery and continuous practice was needed. The implications of this study emphasize the importance of utilizing scaffolding, collaboration, and vocabulary enrichment strategies to improve students' writing independence.